Performance, genetic variation and interrelationships in different traits of some safflower (Carthamus tinctorius L.) genotypes - Hussein, Abdalla; Ibrahim, Abu Elhassan; Hussein, Ismail; Idris, Siddig (المجلة الزراعية; مجلد 16 عدد 2 (2018), 2018)
The success of safflower improvement and production activities can be enhanced with scientific information generated from the study of genotypes, environments and genotype by environment interactions (GEI). In this study, 15 safflower genotypes were evaluated during two consecutive winter seasons (2013/14 and 2014/15) at three locations viz Gezira, El- Suki and Hudeiba Research Station farms of the Agricultural Research Corporation, Sudan. The objectives of this study were to evaluate seed yield potential, the extent of genetic variability and interrelationships in 15 safflower genotypes under different environments in Sudan. Data were collected on days to 50% flowering, days to maturity, plant height (cm), number of branches per plant, number of capitula per plant, number of seeds per capitula, 100 seed weight (g), seed yield (kg/ha), and oil content. A wide range of genetic variability was observed among the genotypes for most of the studied traits. The results also indicated that the tallest genotype (Saff 1) was the latest maturing, and the shortest genotype (Saff 13) was the earliest maturing. Simple linear correlation and path coefficient analyses indicated that days to 50% flowering, plant height, number of branches/plant and number of capitula per plant could be used as potential selection criteria in breeding programs for developing high yielding safflower genotypes. Genotypes Saff 1, Saff 12 and Saff 14 were high yielders (582.4, 507.9 and 572.8, kg/ha, respectively). Also, Saff 14 showed the highest oil content (37.5 %) followed by Saff 12 (31.0 %) and Saff 1 (29.1 %), therefore, they could be grown successfully under irrigated winter condition of central and northern Sudan.       القرطم من المحاصيل الزيتية المهمة في العالم، وفي السودان يزرع المحصول فقط في الولاية الشمالية في المساحة الواقعة علي طول النيل. إن نجاح تحسينِ محصول القرطمِ ونشاطاتِ إنتاجِه يُمْكِنُ أَنْ يُحَسّنا بالمعلومات العلمية التي تنتج منْ دراسة التراكيب الوراثية. قُيّمَت في هذه الدراسةِ خمسة عشرَ تركيباً وراثياً من القرطمَ علي مدي فصلي شتاء متتاليينِ (2013/14-2014/15) في ثلاثة مواقعِ هي محطات بحوث الجزيرة و السوكي والحديبة التابعة لهيئة البحوث الزراعية بالسودان. هدفت الدراسةِ إلي تُقييم هذه التراكيب الوراثية من حيث الانتاجية  ومكوّناتِها و دراسة العلاقات المترابطة بين الانتاجية والصفات المرتبطة بها بإستعمال الإرتباطَ الخطي البسيط و معامل تحليل المسار وتمييز التراكيب الأعلى إنتاجية. كانت الصفات المدروسة هي عدد الأيام حتي 50%  إزهار و عدد الأيام حتي النضج و طول النبات و عدد الفروع بالنبات و عدد الكبسولات بالنبات و عدد البذور بالكبسولة و وزن المائة حبة بالجرام و الإنتاجية بالكيلوجرام للهكتار ونسبة الزيت بالبذور. أوضحت النتائج وجود مدي واسع من التباين الوراثي بين التراكيب الوراثية لمعظم الصفات المدروسة. أوضحت النَتائِج إلي أنّ التركيب الوراثي (Saff 1) هو الاطول من بين التراكيب الوراثية الاخري و متأخر النُضُج، بينما التركيب الوراثي (Saff 13) مبكر النُضُج وهوأقصرالتراكيب الوراثية. من ناحية أخري، باستخدام الارتباط الخطي البسيط ومعامل تحليل المسار، أوضحت الدراسة  أن صفات عدد أيام 50% إزهار و طول النبات و عدد الفروع في النبات و عدد الرؤوس بالنبات يمكن استعمالهما كصفات إنتخاب غير مباشر في برامج التربية لاستنباط أصناف عالية الإنتاجية من القرطم. خلصت الدراسة إلي أن التراكيب الوراثية Saff 1 و Saff 12 و Saff 14 كانت عالية الإنتاجيةً ( 582.4 ، 507.9 و 572.8 :جم/ ه علي التوالي)، كما وأن التركيب الوراثي  Saff 14 له أعلي محتوي من نسبة الزيت  (37.5 %)  يعقبه في ذلك  (31.0 %) Saff 12    و(29.1 %) Saff 1   لذلك يمكن زراعتها بنجاح  تحت ظروف الري الشتوي بأواسط وشمال بالسودان.